The effects of dietary soy protein source fed to the early-weaned pig on subsequent growth performance - K Q Owen; B T Richert; K G Friesen; L J Kats; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1993)
Two hundred and ninety five pigs (initially 12.3 lb and 21 d of age) were used to determine the effect of different soy protein sources fed during phase I on subsequent growth performance. Dietary treatments were based on different soy protein sources added to the phase I (d 0 to 14 postweaning) diet. Pigs were fed one of five experimental treatments: 1) control diet (casein); 2) moist extruded soy protein concentrate (MESPC); 3) soybean meal (SBM); 4) soy protein concentrate (SPC); 5) moist extruded soy flour (MESF). The phase I diet contained 20% dried whey (DW), 7.5% spray dried porcine plasma (SDPP), and 1.75% spray dried blood meal (SDBM) and was formulated to contain 1.6% lysine, .44% methionine, and 14.4% lactose. From d 14 to 28 postweaning (phase II), all pigs were fed a common (1.25% lysine) corn-SBM diet containing 2.5% SDBM and 10% DW. During phase I, no differences occurred in average daily gain (ADG) or feed efficiency (F/G) between any experimental treatments. However, pigs fed the MESPC-based diet had higher average daily feed intakes (ADFI) when compared to pigs fed either SBM or MESF. From d 14 to 28, pigs fed MESPC during phase I, had higher ADG when compared to the performance of pigs fed SPC and MESF and higher ADFI when compared with pigs receiving the other experimental treatments. Pigs fed SBM during phase I had improved F/G compared to SPC and MESPC. Cumulative data (d 0 to 28 postweaning) indicated that pigs fed the diet containing MESPC during phase I had numerically higher ADG and ADFI when compared to pigs fed the MESF or SPC treatments; however, MESPC pigs were less efficient. Feed cost per pound of gain was the lowest for pigs fed SBM during phase I for overall performance. Pigs fed MESPC in phase I had numerically higher ADG and were 1.4 lb heavier at the end of the trial. However, this advantage would cost an additional $2.00 for feed. In summary, economics and performance must be considered before deciding to use SBM or MESPC in the phase I diet. Our results indicate no advantage in using SPC or MESF in the phase I diet.; Swine Day, Manhattan, KS, November 18,1993
Keywords: Swine day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-194-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 695; Swine; Soy protein; Early-weaned pig; Performance